Briefly Noted. (June 2019) - Unknown
Abstract : On March 20, 2019, the Appeals Chamber of the International Residual Mechanism for Criminal Tribunals set aside Radovan Karadžić's prior sentence of forty years and imposed a life sentence. Karadžić was convicted of genocide, crimes against humanity, and violations of the laws or customs of war in March 2016 by a Trial Chamber of the International Criminal Tribunal for the former Yugoslavia and sentenced to forty years in prison. His crimes relate to war crimes he committed during the 1990s conflicts in the Balkans, in particular the 1995 Srebrenica massacre of 8, 000 Bosnian Serbs and the three-year long siege of Sarajevo. The Appeals Chamber reversed part of Karadžić's convictions related to the Overarching JCE and dismissed the rest of his appeal, while also dismissing most of the Prosecution's appeal, aside from the sentence. The Appeals Chamber judges found that the Trial Chamber "committed a discernible error and abused its discretion in imposing a sentence of only 40 years of imprisonment, " and consequently imposed a life sentence.